A new species of Paramoera (Crustacea: Amphipoda: Pontogeneiidae) from an estuary habitat in Hokkaido, Japan. Issue 19 (18th May 2020) - Hagihara, Kumiko; Nakano, Takafumi; Tomikawa, Ko
ABSTRACT: A new species of the pontogeneiid amphipod Paramoera shakotanensis from the mouth of Horonaifu River, Hokkaido, Japan, is described. Paramoera shakotanensis sp. nov. can clearly be distinguished from its congeners by a combination of the following features: large eyes, deep antennal sinus without sharp incision, epimeral plate 3 with smooth posterior margin, small number of setae on inner plate of the maxilla 1 (up to three) and on inner plate with oblique inner row (up to two), pereopod 7 with coxal gill, and distally tapering telson with almost straight lateral margins bearing submarginal setae. http://zoobank.org/urn:lsid:zoobank.org:pub:72E1F36D-87E5-406A-B92D-6DE686150F99